Oromaxillary Prosthetic Rehabilitation of a Maxillectomy Patient Using a Magnet Retained Two-Piece Hollow Bulb Definitive Obturator; A Clinical Report - Jafar Abdulla Mohamed Usman; Anuroopa Ayappan; Dhanraj Ganapathy; Nilofer Nisha Nasir (Hindawi Limited, 2013)
Resection of a malignant lesion involving the maxilla produces severe oromaxillary defect that can seriously jeopardize the normal phonetics of the patient. These defects are effectively managed by well-designed and fabricated obturator. This paper discusses the oromaxillary prosthetic rehabilitation of a maxillectomy patient using a magnet retained two-piece hollow bulb definitive obturator.